2016
DOI: 10.1097/mpg.0000000000001225
|View full text |Cite
|
Sign up to set email alerts
|

CT and MRI of Rare Extraintestinal Manifestations of Inflammatory Bowel Disease in Children and Adolescents

Abstract: Inflammatory bowel disease (IBD) is associated with a spectrum of extraintestinal manifestations (EIMs) affecting many organ systems. EIMs can occur in more than 40% of patients with IBD and are associated with significant morbidity. They occur at any time point in the course of disease, often during an active phase of bowel inflammation, but sometimes preceding bowel disease. Prompt recognition of EIMs enables timely and more effective therapy. Physicians who image patients with IBD should be aware of the myr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 76 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…EIMs are estimated to affect approximately 6% to 47% of adult patients with IBD and around 25% to 29% of pediatric patients with IBD. 4,5 They have been reported to occur more frequently in patients with CD compared with those with UC. 5 A patient may be affected by several EIMs at the same time, given that the presence of one EIM increases the likelihood of developing another.…”
Section: Eimsmentioning
confidence: 99%
See 4 more Smart Citations
“…EIMs are estimated to affect approximately 6% to 47% of adult patients with IBD and around 25% to 29% of pediatric patients with IBD. 4,5 They have been reported to occur more frequently in patients with CD compared with those with UC. 5 A patient may be affected by several EIMs at the same time, given that the presence of one EIM increases the likelihood of developing another.…”
Section: Eimsmentioning
confidence: 99%
“…4,5 They have been reported to occur more frequently in patients with CD compared with those with UC. 5 A patient may be affected by several EIMs at the same time, given that the presence of one EIM increases the likelihood of developing another. 4 A Swiss IBD cohort study showed that 25% of patients with IBD affected by EIMs actually suffered from multiple, in some cases up to five different EIMs.…”
Section: Eimsmentioning
confidence: 99%
See 3 more Smart Citations